KINERJA KELOMPOK USAHA BERSAMA (KUB) NELAYAN GILLNET DI BARSELA ACEH - Muhammad Rizal; Budy Wiryawan; Sugeng Hari Wisudo; Iin Solihin; John Haluan (Bogor Agricultural University, 2017)
ABSTRACTNowadays, the development of fisheries strategic issues is related to poverty and welfare of fishermen. In 2010 - 2014, Ministry of Marine and Fisheries implemented Business Development Program of Rural Area by creating a Joint Business Group (JBG) to help traditional and small scale fishermen who categorized as poor. This study aimed to determine the performance of JBG of gillnet fishermen and to identify the attributes of performance (aspects of institutional, socio-cultural, economic, environmental and policy) in Barsela Aceh. Data was collected by purposive sampling method from 13 JBG of gillnet fishermen. IPA analysis and gap analysis were performed to measure each attribute and attribute's performance. The results showed that the value of the gap in the aspect of the institution of 1.87, and socio-cultural aspect of 1.91, which are categorized as good enough. Furthermore, the value of the economic aspect (2,12), environmental aspect (2,43) and policy aspect (2.21) are categorized as less good. The attributes which categorized as a top priority (in quadrant A) are the aspect of institution, namely; human resources quality of JBG, the level of utilization of information technology and marketing, participation in training event, frequency of training held by related agencies and traditional institutions and the effectiveness of PPTK. Socio-cultural aspects are the desire to be independent culture, work ethic culture, group cohesiveness, and JBG assets are jointly managed. In economic aspect are active savings and loan activities, the level of turnover development of JBG and the level of market opportunities for JBG fishermen's business. Environmental aspects are the effectiveness of target fish species catch, high economic value of fish and environment-friendly technologies. Policy aspects are sanctioned policies for fictitious JBG, policies about who can become a member of JBG, policy management in preparing a joint business plan and sanctions for members who violate the rules.Keywords: Barsela Aceh, JBG, gillnet fishermenABSTRAKPerkembangan isu strategis perikanan saat ini adalah kemiskinan dan kesejahteraan nelayan. Kementerian Kelautan dan Perikanan Tahun 2010-2014 melaksanakan Program Pengembangan Usaha Mina Perdesaan (PUMP) dengan membuat Kelompok Usaha Bersama (KUB) untuk membantu nelayan tradisional dan kecil yang masih tergolong miskin. Penelitian ini bertujuan yaitu mengetahui kinerja KUB nelayan gillnet dan mengidentifikasi atribut kinerjanya (aspek lembaga, sosial budaya, ekonomi, lingkungan dan kebijakan) di Barsela Aceh. Metode pengambilan data purposive sampling, dimana data diambil secara sengaja pada 13 KUB nelayan gillnet. Analisis data yang digunakan yaitu analisis IPA untuk menilai setiap atribut dan analisis kesenjangan (gap) untuk menilai kinerja setiap atribut. Hasil penelitian menunjukkan bahwa nilai kesenjangan pada aspek lembaga (1,87) dan aspek sosial budaya (1,91) yaitu katagori cukup baik. Selanjutnya nilai pada aspek ekonomi (2,12), aspek lingkungan (2,43) dan aspek kebijakan (2,21) yaitu katagori kurang baik. Serta atribut yang prioritas yaitu posisi atribut kuadran A (diprioritaskan) pada aspek lembaga adalah kualitas SDM KUB, tingkat pemanfaatan akses informasi teknologi dan pemasaran, keikutsertaan kegiatan pelatihan, intensitas pembinaan dari instansi terkait dan lembaga adat dan keefektifan PPTK. Aspek sosial budaya adalah budaya ingin mandiri, budaya etos kerja, kekompakan kelompok, dan aset KUB dikelola secara bersama. Aspek ekonomi adalah aktifnya kegiatan simpan pinjam, tingkat perkembangan omset KUB dan tingkat peluang pasar untuk usaha KUB nelayan. Aspek lingkungan adalah efektivitas jenis ikan target yang tertangkap, ikan ekonomis tinggi dan teknologi ramah lingkungan. Aspek kebijakan adalah aturan sanksi bagi KUB fiktif, kebijakan tentang yang bisa menjadi anggota KUB, kebijakan manajemen dalam menyusun rencana usaha bersama dan aturan sanksi bagi anggota yang melanggar.Kata kunci: Â Barsela Aceh, KUB, nelayan gillnet